IDENTIFIKASI SUB SEKTOR PERTANIAN DI EKS KARESIDENAN KEDU (PENDEKATAN MINIMUM REQUIREMENTS TECHNIQUE) - Dinan Azifah; Agustono Agustono; Nuning Setyowati (Universitas Sebelas Maret, 2016)
The objectives of this study are (1) identify the Agricultural sub sector of base and non-base in Kedu Residency (2) develop the Agriculture sub sector of base in Kedu Residency. The results, the food crops subsector basis in Kebumen, Magelang,Wonosobo, Temanggung. Sub Sector Crops base in Kebumen, Purworejo, Magelang, Temanggung. Livestock subsector base in Kebumen, Magelang, Wonosobo, Temanggung. Forestry subsector base in Kebumen, Purworejo, Magelang, Wonosobo.Fisheries subsector base in Kebumen, Purworejo, Magelang, Wonosobo. Food crops subsector non bases in Purworejo, plantation subsector in Wonosobo, livestock subsector in Purworejo, forestry and fisheries subsector in Temanggung. Development of food crops subsector in Kebumen to maximize production, agribusiness development in Magelang, in Wonosobo processing performed and marketing, in Temanggung the marketing of agricultural products. Development of the plantation subsector in Kebumen the development of HR trained, in Purworejo improving the marketing, in Magelang the development of conservation areas, in Temanggung increasing marketing and post-harvest processing. Development of the livestock subsector in Kebumen providing capital strengthening, in Magelang increased productivity through improved genetic quality, in Wonosobo revolsin Funds budgeted for the farm, in Temanggung increase in value-added farm. Development of the forestry subsector in Kebumen, Purworejo, and Wonosobo did by developing a variety of non-timber business, in Magelang conservation of forest resources. Development of the fisheries subsector in Kebumen improving the marketing, in Purworejo increase fisheries production, in Magelang managing and marketing of fisheries production, in Wonosobo provision of adequate infrastructure.